Evaluating Unemployment Policies : What Do the Underlying Theories Tell Us? - Snower, Dennis (IMF Working Papers; Working Paper ;, 1995)
The paper surveys unemployment policies for advanced market economies and evaluates them by examining the predictions of the underlying macroeconomic theories. The basic idea is that, for the most part, different unemployment policy prescriptions rest; on different macroeconomic theories, and our confidence in the prescriptions least in part--on the theories' ability to predict some salient stylized facts about unemployment behavior. The paper considers four types, of policies laissez faire, demand-management supply-side; and structural policies.